Effect of constrained sintering on the piezoelectric properties of PZT thick films - Tillman, Mark (Cranfield University, 2012)
This thesis concerns the processing of thick lead zirconate titanate (PZT) films integrated with rigid substrates. The aim was to better understand the evolution of the microstructure, stress, and electrical properties of the films under constrained sintering conditions. This is an important process to understand because of the degrading effects that constrained sintering has on PZT films, which are employed vastly in commercial applications. It is hypothesised that the better understandings can lead to the development of PZT films that exhibit superior dielectric and piezoelectric properties than those in current production. The shrinkage of PZT films was examined in order to better understand the ways in which the rigidity of the substrate affects densification during sintering. This was done by processing isolated regions of PZT film on silicon substrates. These were sintered using a halogen bulb which exhibited a spot at a temperature of 725°C and with a ramp rate of less than 10 seconds. In this way the sintered regions could be ‘frozen’ mid sintering. The shrinkage of the films was determined at various sintering times. It was found that film shrinkage had finished within 2 minutes of sintering. The evolution of the constrained films during sintering was then examined as a function of the microstructure, stress and electrical property development. It was found that the grain sizes and electrical properties increased within 2 minutes of sintering. However, at longer sintering times there was a degradation of the films. Furthermore, tensile stresses developed during sintering which had degrading effects. This work was expanded upon by motioning the PZT films in a single line scan through the sintering spot to sinter larger areas of the film in one motion. This resulted in a high control over the sintering times, which was vital as the highest electrical properties were found at short sintering times. Next it was examined if the electrical properties could be further increased by applying a compressive stress. It was found that the dielectric properties increased as a result of increased domain wall vibrations. However, there was a decrease in domain reorientation during poling as a result of the effect of the compressive stress, thus the piezoelectric properties reduced. The evolution of PZT films under constrained sintering was better understood as a result of these studies, and led to the development of a sintering method in which the dielectric and piezoelectric properties were increased.